Application of Artificial Intelligence in transport in the face of driver shortage - legal, ethical and technical aspects - Pakuła, Zuzanna; Peruga, Anna; Śnieguła, Dominika (Contemporary challenges of transport, freight forwarding and logistics - selected aspects, 2023)
The aim of the chapter is to present the technical and legal aspects of the application of Artificial Intelligence in transport in the context of the driver shortage. The authors first outlined the problem of driver vacancies in Poland and the EU, and then presented the technical and legal-ethical considerations for the application of Artificial Intelligence in this area.